Numerical simulation on the effect of concentration on premixed CH4/CO2/air explosion characteristics - Nur Aqidah, Muhammad Harinder Khan; Siti Zubaidah, Sulaiman; Izirwan, Izhab; Siti Kholijah, Abdul Mudalip; Rohaida, Che Man; Shalyda, Md Shaarani; Zatul Iffah, Mohd Arshad; Kasmani, R. M.; Sarina, Sulaiman (Universiti Malaysia Pahang, 2019)
In this study, a numerical simulation on the premixed CH4/CO2/air (methane/carbon dioxide/air) mixture explosion characteristics was conduted by using the Flame ACcelaration Simulator (FLACs) software. The domain used in the 20 L spherical vessel with 0.808 m diameter. The effect of various equivalence ratios on the explosion characteristics such as the explosion pressure, Pex, maximum explosion overpressure, Pmax, the maximum rate of pressure rise, (dP/dt)max and gas deflagration index, KG, were studied. For this purpose, the mixture concentrations range from equivalence ratio (ER) 0.8 to 1.5 (9.6 to 18% vol/vol) were considered. From this study, the explosion pressure, Pex, maximum explosion overpressure, Pmax, the maximum rate of pressure rise, (dP/dt)max, at various ER was the maximum at a slightly rich concentration (ER=1.2). At lean and rich mixtures, the Pex, Pmax, (dP/dt)max and KG decreases. It can be said that, at ER=1.2, the role of thermal-diffusive instability and its effets on the flame speed during the pressure development process dah causes the diffused methane, CH4 present in the lean and rich mixtures. The CH4/CO2/air mixtures studied in this study were also found to have the highest level of hazard potential when exploded.